Fabrication Of Bismuth Oxychloride / Reduced Graphene Oxide Composites For Visible-Driven Photocatalysis - Nguyen-Thi, Bao-Ngoc; Nguyen-Thi, Thuy-An; Huynh, Quoc-Cuong; Nguyen, Kim Thi; Pham, Thanh-Truc (Journal of Technical Education Science, 2025)
In this study, the BiOCl/rGO (BR) nanocomposites were fabricated via different pathways, BiOCl nanocrystals were directly grown on graphene oxide (GO) sheets and BiOCl nanoflowers and GO were attached after individual fabricated. The basic properties and structures of BiOCl, GO and BR were evaluated by convert infrared spectroscopy (FT-IR), X-ray diffraction spectroscopy (XRD), Raman scattering spectroscopy and scanning electron microscope (FE-SEM). In this case, the direct growth of BR1S performed stronger linkage between BiOCl and rGO through the chemical interaction of the Bi-C band. That interaction reduced the size of the BR, and showed that the electrons were more excited. Results in the improvement of reaction rate constant 1.45 times higher than the pristine BiOCl, which can totally remove RhB 10 ppm in 30 min.